PAI-1 level and the PAI-1 4G/5G polymorphism in relation to risk of non-fatal myocardial infarction - Leander, Karin; Wiman, Björn; Hallqvist, Johan; Sten-Linder, Margareta; de Faire, Ulf (Thrombosis and Haemostasis, 2003)
This study examines the relationship between plasma Plasminogen Activator Inhibitor-1 (PAI-1) activity and the PAI-1 4G/5G polymorphism, and their association with the risk of myocardial infarction (MI). Furthermore, this study explores whether a high level of PAI-1 or whether the PAI-1 4G/5G polymorphism synergistically interacts with any established environmental risk factor for MI. This case-referent study of subjects aged 45-70 and living in Stockholm includes 851 men and 361 women with first-time MI and 1051 men and 505 women who were randomly chosen as referents from a population register. The adjusted odds ratio (OR) of MI was 1.9 (95% confidence interval [CI] 1.4-2.8) for men with a plasma PAI-1 activity level greater than the 90th percentile value of referents. The corresponding OR for women was 1.5 (95% CI 0.9-2.5). A strong indication of synergistic interaction was found in men for the co-exposure to high plasma PAI-1 activity and current smoking, an adjusted synergy index score of 3.9 (95% CI 1.2-13.2). In women, the 4G allele was associated slightly with an increased risk of MI, OR 1.4 (95% CI 1.0-1.9). This association was not found in men. There were no clear indications of synergistic interaction effects involving the PAI-1 4G/5G polymorphism and the environmental exposures considered (cigarette smoking, physical inactivity, overweight, diabetes mellitus, hypercholesterolaemia, hypertension, high C-reactive protein and hypertriglyceridaemia).
Keywords: Myocardial infarction; PAI-1; 4G/5G polymorphism; interaction